Case report: Torsade de pointes induced by the bigeminy result from retrograde ventriculoatrial activation in VVI pacing and resolved by intentional atrial pacing - Chu, Song-Yun; Sheng, Qin-Hui; Shi, Qiu-Ping; Qiu, Lin; Wu, Lin; Zhou, Jing (Frontiers in Cardiovascular Medicine, 2023)
Introduction While pacing has been used for long QT syndrome (LQTs), the optimal pacing modality is controversial. Case We report a woman with bradycardia and a recently implanted single-chamber pacemaker experienced multiple syncope. No device dysfunction was found. Multiple Torsade de Pointes (TdP) induced by the bigeminy result from retrograde ventriculoatrial (VA) activation in VVI pacing were demonstrated in the scenario of previously unidentified LQTs. Replacement for a dual-chamber ICD and intentional atrial pacing eliminated the VA conduction and symptoms. Conclusion Pacing without atrioventricular sequence might be catastrophic in LQTs. Atrial pacing and atrioventricular synchrony should be highlighted.